The Effect of Students Vocabulary By Using Audio Visual Media At University Of Esa Unggul - Ananda Krismonita A; Yon A E (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
This research is aimed to find out the effect of students vocabulary by using audio visual media compared with students who learned vocabulary without using audio visual media. It is an experimental research. This research was conducted with the participants of 40 students’ from University of Esa Unggul. The data was obtained through pre test and post test. This study compare mean average between pre test and post test to find out students response toward Audio Visual Media. Furthermore, the results show that teaching vocabulary by using audio visual media give effect on the students vocabulary. The mean score of pre test was 67,40 and the mean of post test was 86,05. Its mean that there was significant effect of students vocabulary using audio visual media at University of Esa Unggul.